Desertification and agricultural productivity: Evidence from 5,636 grids - Maurizio Malpede; Marco Percoco (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2021)
The economic effects of global warming have gained considerable attention in recent economic literature. However, the interaction between desertification and agricultural productivity has not received substantial consideration. In this paper, we explore the relationship between soil aridification (a process that considers both precipitation and potential evapotranspiration of the soil) and agricultural productivity. Our most conservative estimates show that the process of aridification, having occurred from 1995 to 2005, was associated with a decline in agricultural output of between 0.4 and 1.1 tons per hectare of cultivated cropland in Africa and of between 0.1 and 0.5 tons per hectare of cultivated cropland in Asia.
Keywords: O13; Q54; Q56; 330; Aridification; Climate Change; Agricultural Productivity; Desertification